Revisiting analytical solutions for steady interface flow in subsea aquifers: Aquitard salinity effects. (June 2018) - Werner, Adrian D.; Robinson, Neville I.
Highlights: Subsea fresh groundwater analytical solution revised to include aquitard salinity. Comparison to numerical modeling demonstrates aquitard salinity effects. Solution produces improved discharge to the sea and interface tip location. Further work is required to assess dispersion effects on interface distribution. Abstract: Existing analytical solutions for the distribution of fresh groundwater in subsea aquifers presume that the overlying offshore aquitard, represented implicitly, contains seawater. Here, we consider the case where offshore fresh groundwater is the result of freshwater discharge from onshore aquifers, and neglect paleo-freshwater sources. A recent numerical modeling investigation, involving explicit simulation of the offshore aquitard, demonstrates that offshore aquitards more likely contain freshwater in areas of upward freshwater leakage to the sea. We integrate this finding into the existing analytical solutions by providing an alternative formulation for steady interface flow in subsea aquifers, whereby the salinity in the offshore aquitard can be chosen. The new solution, taking the aquitard salinity as that of freshwater, provides a closer match to numerical modeling results in which the aquitard is represented explicitly.